Students’ Experience, Self-Confidence, and Perception Toward Endodontic Learning: National Survey Among Malaysian Dental Schools - Omar, Siti Hajar; Alias, Aspalilah; Baharin, Safura Anita (UI Scholars Hub, 2023)
Objective: This study aimed to evaluate the first endodontic case experiences, self-confidence levels, and perceptions toward endodontic learning of final-year undergraduate students. Methods: An online questionnaire was emailed to 270 final-year dental students at 10 Malaysian dental schools. The questionnaire consists of 29 questions on students’ experience, self-confidence, and perception toward endodontic learning. Results: The response rate was 74.4%. The most frequently treated case was tooth diagnosed as nonvital associated with periapical periodontitis. Most of the students perceived working length determination as the most difficult stage and reported having low confidence in locating canal orifices in multirooted teeth and achieving satisfactory obturation. Overall, the students were satisfied with the endodontic knowledge taught by their respective faculties. Conclusion: Endodontic teaching in Malaysian dental schools was perceived as satisfactory by most dental students. Although endodontic treatment is perceived as difficult, students demonstrated high confidence in carrying out this treatment. However, they had limited ability in treating the complex root canal system.